The Oogenesis of Sclerectinian Corals Caulastrea furcata and Lobophyllia corymbosa - MUJIZAT KAWAROE; DEDI SOEDHARMA; MAULINIA MAULINIA (Bogor Agricultural University, Indonesia, 2007)
Caulastrea furcata and Lobophyllia corymbosa are corals of order Sclerectinian. Caulastrea furcata is the only species of genus Caulastrea that could be found in Kepulauan Seribu and L. corymbosa is a rare species. The purpose of this research was to study sexual reproduction of the Sclerectinian coral. The result showed that the ovaries of C. furcata and L. corymbosa were developed in the mesentery, inside the mesoglea, and pinched by gastrodermis. Distinctive channel with trophonema like structure was found in both species as well as gamete which was spawned from polyp through distinctive channel. The gamete simply spawned trough gastrodermis, heading from mesentery filament to excretion track. Histological observation showed that there were four stages of gamet maturity level. However, gonad maturity level consisted of three stadia depended on the characteristic of the ovary. Key words: oogenesis, sexual, reproduction, corals Caulastrea, Lobophyllia, Seribu Island